Critical market studies: a proposal for politically engaged expansion of marketing theme: a proposal for politically engaged expansion of marketing themes - Luna Batinga, Georgiana; Pinto, Marcelo de Rezende (Perspectivas Contemporâneas, 2024)
This article aims to propose a research agenda to articulate market studies and critical marketing. Discussions were developed about the concept of market and marketing, about the movement known as studies of market dynamics, as well as notes on critical marketing. We conclude that the various dysfunctions which business activities can cause cannot be addressed by observing only their dynamics and the relations among their actors. It is necessary to create a path that includes the moral and political aspects of markets, their wrongdoings, illegalities, as well as their dark, dirty and sometimes clandestine side. This is only possible by adopting a critical and denunciative orientation, committed to the goal of removing the "veil" that covers these issues, historically erased from the marketing debates that can be represented by critical marketing.